Experimental evidence of the effect of monetary incentives on cross-sectional and longitudinal response: Experiences from the Socio-Economic Panel (SOEP) - Mathis Schröder; Denise Saßenroth; John Körtner; Martin Kroh; Jürgen Schupp (Deutsches Institut für Wirtschaftsforschung (DIW), 2013)
The paper gives an overview of two experiments implemented in the German Socio-Economic Panel (SOEP) considering the effect of monetary incentives on cross-sectional and longitudinal response propensities. We conclude that the overall effects of monetary incentives on response rates are positive compared to the classic SOEP setting, where a charity lottery ticket is offered as an incentive. In the cross-section, cash incentives are associated with a higher response rate as well as a lower rate of partial unit non-response (PUNR) and fewer noncontacts on the household level. Separate analyses for German and immigrant households show that a monetary incentive has a positive effect on immigrant households' participation in subsequent waves. Regarding the regions where the households are located, the high cash incentive has a positive effect on response rates in provincial towns and rural areas. The incentive treatment decreases the likelihood of PUNR in the longitudinal setting by motivating members of participating households who had refused to participate in previous waves to respond in subsequent waves.
Keywords: 330; incentive experiment; response rates; partial unit nonresponse; nonresponse bias; conditional incentives